The definition of the base (wholesale) electricity prices for industrial consumers - Дорошенко, Олександр Іванович; Романюк, Олена Вікторівна; Пєсков, Сергій Анатолійович; Борисенко, Світлана Олександрівна (Technology audit and production reserves, 2015)
Based on the physics of normal operation power, the paper proposed a new science-based approach to determining the price of electricity for industrial and equated to them customers, in which voltage electric networks is seen as a potential form of electricity and network with nominal voltage 110 kV serve as counter energy market of Ukraine. Given that pricing in the electricity system is the basic calculation system, which determines its functioning economy, it is proposed the vote at two levels: the base (wholesale) and retail. The principles for determining the base (wholesale) prices for electricity, which take into account the physics of power transmission based on the properties of concept consumer connection to system networks with a voltage of 110 kV are considered and the approach to the development of methods for determining the retail price of electricity is outlined.